ROLE OF LAPAROSCOPY IN EVALUATION OF ABDOMINAL PAIN: Laparoscopy in Evaluation of Abdominal Pain - Masud, Mannan; Adil, Muhammad; Iqbal Gondal, Zafar; Aquil, Adnan; ., Zainab; Jahangeer, M Hamza; Ahmed, Mamoon (Pakistan Armed Forces Medical Journal, 2017)
Objective: To evaluate the diagnostic efficacy of laparoscopy in ill-defined recurrent chronic abdominal pain.Study Design: Prospective study.Place and Duration of Study: Surgical department, Military Hospital Rawalpindi, from Jul 2011 to Dec 2013.Material and Methods: A total of 102 patients who presented to surgical department with chronic recurrent abdominal pain of unknown etiology and underwent diagnostic laparoscopy were included in our study. Patients with acute onset of abdominal pain, hemodynamically unstable, pregnant or those in which diagnosis can be made by radiological techniques were excluded from our study. Patient’s demographic data, clinical findings and laparoscopic findings were recorded. Finally data was analyzed by using SPSS version 21.Results: Out of 110 patients 96 were female while remaining 14 were male. The age range of the patients was 20- 70 years with mean age of 50 ± 10 years. The most common site of pain was lower abdomen while mean duration of abdominal pain was 34 weeks. Laparoscopic findings include acute recurrent appendicitis in 32 (29.09%) patients, cholecystitis with biliary sludge in 14 (12.72%), pelvic inflammatory disease in 12 (10.90%), ovarian cyst in 11(10%), adhesions in 10(9.09%), intestinal tuberculosis in 8 (7.27%), mesenteric lymphadenitis in 7 (6.36%), lymphoma in 4 (3.63%), ectopic pregnancy in 3 (2.7%), CA gallbladder in 2 (1.81%), meckels diverticulum in 2 (1.81%), endometriosis in 2 (1.81%) and crohns disease in 1 (0.9%) patients. Mean operative time was 48 min while average hospital stay was 2-3 days. No major complications were noticed.Conclusion: Laparoscopy in our clinical setup has significant role in diagnosing cases of vague abdominal pain which cannot be diagnosed by routine investigations.